The ubiquitin-proteasome system in Alzheimer’s disease: mechanism of action and current status of treatment - Jia, Shanshan; Li, Quan; Rui, Xue; Qin, Wen; Zhang, Wenhui; Dou, Jinjin; Zhang, Xiwu (Frontiers in Aging Neuroscience, 2025)
Alzheimer’s disease (AD) is one of the most common neurodegenerative disorders; current therapies can neither cure AD nor prevent its progression. The pathological hallmark of AD is the excessive deposition of abnormal proteins in the brain, primarily including β-amyloid (Aβ) and phosphorylated Tau proteins. The ubiquitin-proteasome system (UPS), a central intracellular protein degradation mechanism that removes misfolded proteins and maintains cellular homeostasis by inhibiting aberrant protein aggregation, plays an important role in the regulation of various physiological functions, as well as in the development of disease. Any abnormality in this process leads to protein misfolding and aggregation, and the accumulation and aggregation of ubiquitinated proteins is a common feature of many neurodegenerative diseases, including AD. A growing number of studies have confirmed the significance of UPS in the AD process, which may act in conjunction with other mechanisms leading to the development of AD, and may even be the direct cause of AD. UPS offers a whole new possibility for the development of drugs for AD prevention and treatment, as well as new strategies and approaches for the treatment of neurodegenerative diseases. Therefore, this review is based on UPS, describes the possible mechanisms of action of UPS in AD, and summarizes the preclinical studies of modulating UPS for the treatment of AD.